Musical salon culture in the long nineteenth century - Bunzel, Anja ca. 20./21.Jh; Loges, Natasha ca. 20./21. Jh (The Boydell Press, 2019)
This collection explores the idea of music in the salon during the long nineteenth century, both as a socio-cultural phenomenon, and as a source of artistic innovation and exchange. Drawing on a wide range of scholarly approaches, this book uses the idea of the salon as a springboard to examine issues such as gender, religion, biography and performance; to explore the ways in which the salon was represented in different media; and to showcase the heterogeneity of the salon through a selection of case studies. It offers fresh considerations of familiar salons in large cultural centres, as well as insights into lesser-known salons in both Europe and the United States. Bringing together an international group of scholars, the collection underscores the enduring impact of the European musical salon